2020
DOI: 10.1111/ctr.14061
|View full text |Cite
|
Sign up to set email alerts
|

Role of a cardio‐renal multi‐disciplinary team meeting in managing cardiovascular risk in patients on kidney transplant waitlists

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A multidisciplinary cardiology-nephrology service with doctors and specialist nurses in the United Kingdom has demonstrated better utilization of evidence-based therapy and health care resources (51). A similar multidisciplinary meeting for prekidney transplant patients, with cardiologists, nephrologists, transplant surgeons, and specialist nurses, showed that high-cardiac-risk patients can be safely transplanted (52).…”
Section: Multidisciplinary Carementioning
confidence: 99%
“…A multidisciplinary cardiology-nephrology service with doctors and specialist nurses in the United Kingdom has demonstrated better utilization of evidence-based therapy and health care resources (51). A similar multidisciplinary meeting for prekidney transplant patients, with cardiologists, nephrologists, transplant surgeons, and specialist nurses, showed that high-cardiac-risk patients can be safely transplanted (52).…”
Section: Multidisciplinary Carementioning
confidence: 99%
“…[ 15 ] described the usefulness of a monthly cardio-nephrology meeting to provide expert consensus decision-making, reducing unnecessary outpatient visits. Specialized cardiorenal care has also been developed in other clinical scenarios with promising results, such as in hospitalized patients with concomitant heart and kidney disease or in high-risk kidney transplant candidates [ 16 , 17 ].…”
Section: The Need For Cardiorenal Programsmentioning
confidence: 99%
“…Currently, the benefits of the multidisciplinary handling of patients with congestion and cardiorenal syndrome has been reported [ 19 , 20 ]. Moreover, in many hospitals, these patients are treated early by a team involving cardiologists and nephrologists in cardiorenal units.…”
Section: Therapeutic Approachesmentioning
confidence: 99%